AC–AC power electronic converters without DC energy storage: A review. (1st March 2015) - Szcześniak, P.; Kaniewski, J.; Jarnut, M.
Highlights: The review of AC–AC power converters, without DC energy storage elements are shown. A limitations of such systems are depicted. Basic properties and regulation ranges of presented converters are shown. The comprehensive comparison of component complexity and basic properties of such converters is presented. Abstract: The development of power converter topologies, with an increased number of components seems to be an interesting option in modern applications, especially in terms of reliability, efficiency, and current or voltage distortions improvement. This paper focuses on AC–AC power converter technologies without DC-link energy storage elements. The presented converter topologies are fully solid state devices with small passive elements, which are implemented to filter off the high frequency current or voltage components. In the paper the converters are categorized into two groups: with constant output frequency, and with variable output frequency. The first group includes topologies of matrix and matrix-reactance choppers. The second group includes frequency converters based on the matrix converter, taking into account indirect (indirect matrix converter, sparse matrix converter) and multi-level topologies (three-level-output-stage indirect matrix converter, indirect three-level sparse matrix converter, multimodular matrix converters), as well as the topology allowing an increase in the output voltage (matrix-reactance frequency converters). Various converter topologies are presented, compared, and evaluated against output voltage and phase control, input power factor control, and number of components. The features of each converter configuration are considered in the context of alternative applications for commonly used converters with DC-link energy storage devices.